Kokedama: Teknik Inovatif untuk Meningkatkan Peluang Bisnis Tanaman Hias di Palembang, Sumatera Selatan - Meli Astriani; Saleh Hidayat; Wulandari Saputri (Universitas Mathla'ul Anwar Banten, 2022)
KOKEDAMA: AN INNOVATİVE TECHNİQUE TO INCREASE ORNAMENTAL PLANT BUSİNESS OPPORTUNİTİES İN PALEMBANG, SOUTH SUMATERA. Kokedama is a unique planting technique from Japan. Plants are planted in a planting medium from the soil in the form of balls covered by moss plants. Kokedama can be modified by replacing the soil wrap from moss with coco fibre which is usually considered waste and not used. In Indonesia, many people, especially housewives, have a hobby of planting and collecting ornamental plants. However, only using conventional planting media such as plastic or stone pots. Kokedama training is considered appropriate to be given to today's society. This service aims to introduce innovations in making ornamental plants with the kokedama technique and to train these skills. The training method used is participatory, with 20-25 participants who are housewives. The resource persons demonstrated these skills, and the participants immediately practised them in groups. The result of this activity is that participants master the skills of making ornamental plants with the kokedama technique. Thus, the participants will be able to use these skills to increase the selling value of ornamental plants and, in the end, can help improve the economy of their families.